THE LIFE AND WORK OF ENLIGHTENER ABDULLA AVLONI (American Journal of Interdisciplinary Research and Development, 2023)
This article will help to reveal the bright aspects of the life and work of Avloni, the great scholar of Uzbek literature, his pedagogical activity, and his contribution to literature. At the same time, it contains valuable information that is not available in the school textbook. That's why this article is important.